1960
DOI: 10.1084/jem.111.5.643
|View full text |Cite
|
Sign up to set email alerts
|

Specific and Non-Specific Immunity in Experimental Cryptococcosis in Mice

Abstract: Host defense mechanisms often appear to be inadequate following cryptococcal invasion (1-4). Significant antibody response has not been demonstrated with any regularity in man or experimental animals during torula infection. Furthermore, cellular response in cryptococcosis is frequently sparse. The apparent inadequacy of host antibody and cellular defenses during torula infection has been related to the presence of a large capsule, surrounding the cryptococcus cell, which consists primarily of several polysacc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
26
0
1

Year Published

1960
1960
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 16 publications
1
26
0
1
Order By: Relevance
“…Populations were similar in cortisone-treated and control mice 15 minutes to 24 hours after infection. Candida clearance was delayed in mice treated with cortisone.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…Populations were similar in cortisone-treated and control mice 15 minutes to 24 hours after infection. Candida clearance was delayed in mice treated with cortisone.…”
Section: Resultsmentioning
confidence: 82%
“…Liver and spleen were also used for fungus enumeration in Cryptococcus experiments after it was shown that progressive infection occurred in all organs studied including liver-spleen (which were combined), lung, kidney, and brain during the first 2 weeks after infection (15). Subsequently, more detailed quantitative studies in this laboratory have demonstrated that multiplication during the first 2 weeks was somewhat less in the liverspleen than in the lungs, kidney, and brain.…”
mentioning
confidence: 99%
“…For example, multiple reports have documented that wildtype strains vary in animal pathogenicity [10][11][12][13] and the expression of virulence phenotypes, such as the size [ 14 ], composition [ 14 , 15 ] and biological activity of the capsule [ 16 ], production of laccase [ 17 ] and phospholipases, susceptibility to antifungal drugs, and resistance to phagocytosis and phagocytic killing mechanisms [ 12 , 18-20 ]. Many genome-wide approaches are designed to compare multiple strains and to investigate microbial populations rather than a small number of laboratory strains.…”
Section: Cryptococcus Neoformansmentioning
confidence: 99%
“…Without entering into a detailed discussion of the various modalities used, it should suffice to enumerate the names of those who participated in these experiments. Hoff [6] v/as the trailblazer who used heat-killed cryptococci, who was followed by Kligman [7], G adebusch [4,5], Louria [8], Louria el at. [9], Louria and Kaminski [10], Marcus and Rambo [11], Abrahams and G illeran [I] and Abrahams [2], The latter combined heat-and formalin-killed cryptococci with Bordetella pertussis vaccine and achieved a survival rate of approximately 100%.…”
mentioning
confidence: 99%